2019
DOI: 10.3201/eid2503.180600
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Lymphogranuloma Venereum, Buenos Aires, Argentina

Abstract: Among 34 men with proctitis in Buenos Aires, Argentina, 16 (47%) had Chlamydia trachomatis infection, 11 (68.8%) of which were biovar lymphogranuloma venereum. The outbreak was probably local, as in Europe. In Argentina, lymphogranuloma venereum should be a suspected cause of proctitis in HIV-infected men who have had unprotected anal sex with men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Data on LV epidemiology showed that the disease is still endemic in Africa, Asia and South America. A recent study from Buenos Aires, Argentina, found that among the samples of men with CT proctitis, the majority (68.8%) were positive for L2 genotypes 3 . Previously considered rare in the Western Countries, an outbreak in the Netherlands in 2003 brought LV attention and more cases are now being reported in Europe as well as other high‐income countries, especially among human immunodeficiency virus (HIV)‐infected men who have sex with men (MSM).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Data on LV epidemiology showed that the disease is still endemic in Africa, Asia and South America. A recent study from Buenos Aires, Argentina, found that among the samples of men with CT proctitis, the majority (68.8%) were positive for L2 genotypes 3 . Previously considered rare in the Western Countries, an outbreak in the Netherlands in 2003 brought LV attention and more cases are now being reported in Europe as well as other high‐income countries, especially among human immunodeficiency virus (HIV)‐infected men who have sex with men (MSM).…”
mentioning
confidence: 95%
“…genotypes. 3 Previously considered rare in the Western Countries, an outbreak in the Netherlands in 2003 brought LV attention and more cases are now being reported in Europe as well as other high-income countries, especially among human immunodeficiency virus (HIV)-infected men who have sex with men (MSM).…”
mentioning
confidence: 99%
“…In this study, CT was found in almost half of the patients with anorectal complaints presumably secondary to an STI, with a significant predominance of LGV strains. In 2018, our group reported an outbreak of LGV in Buenos Aires, Argentina, 5 similar to the European ones. In Latin-America, there were only isolated cases published of anorectal LGV without genotyping until that year.…”
Section: Discussionmentioning
confidence: 53%
“…3,4 Similarly, in 2018 an outbreak of anorectal LGV was reported in Argentina particularly among men who have sex with men (MSM) living with HIV (LHIV). 5…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, an outbreak of rectal lymphogranuloma venereum causing acute proctitis, particularly in men who had sex with men who were infected with HIV (as in the European outbreak), was reported in Argentina, 4 leading the Argentinian health authorities to issue an epidemiological alert. We analysed anal swabs from patients with anorectal signs or symptoms of proctitis in private practice and a public hospital.…”
mentioning
confidence: 99%